If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -3y = 41 Solving X + -3y = 41 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '3y' to each side of the equation. X + -3y + 3y = 41 + 3y Combine like terms: -3y + 3y = 0 X + 0 = 41 + 3y X = 41 + 3y Simplifying X = 41 + 3y
| 5z+15=25 | | -10(b-5)=-100 | | 3(n+44)=18 | | -10(b-5)=-1000 | | 8(3x+2)=50 | | 3a+6=6a-5 | | 4(2a+6)=80 | | 9x-3x-4x= | | 43=x+.08625x+.2x | | -10(b+5)=-1000 | | 9x-3x-4x=0 | | 9/877x=49.67 | | -50(b+5)=-1000 | | 10y-7=73 | | -2/3(4x-7)=14 | | 4x+20=44 | | 3x^2-2x-6-8x+7-2x^2= | | 7(t+4)-3(t+5)=13 | | -50(b-5)=-1000 | | 7x-7(x-7)=24x+5 | | (4x+4)=(74-x) | | y=-3.5x^2+210x | | 2.5x+16=-4 | | 7x-(7)=24+5x | | -50(b-5)=500 | | 8y-3=179-2y | | 2(x-4)-(6+x)=3x-4 | | ln(2-x)=0.5 | | =2(5g^2-14g+8) | | 7p+6=17 | | 4t+23=11t-2 | | 9=3/4(-12x+36) |